1996
DOI: 10.1099/0022-1317-77-9-2193
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Activity of Sequences Located Upstream of the Human Papillomavirus Types 16 and 18 Late Regions

Abstract: The regulation of human papillomavirus (HPV) late gene expression is difficult to analyse because the late proteins L1 and L2 are only produced in the upper layers of terminally differentiated keratinocytes. However, for the minor capsid protein L2 of HPV types 1, 6, 11 and 16, rare mRNAs or cDNAs starting 3" of the E5 open reading frame (ORF) were previously described. In order to analyse whether the DNA region preceding the late ORFs (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Specifically, compared to the HPV-16R sequence, CaSki HPV-16 has no frameshift or nonsense mutations in any ORFs, and none of the nucleotide changes in CaSki HPV-16 alter established HPV-16 splice donor or acceptor sites, polyadenylation signals or transcription factor binding motifs (Human Papillomaviruses, 1995). The nucleotide changes in the CaSki HPV-16 SNR in full-length genomes could decrease mRNA stability or affect late promoter activity (Geisen & Kahn, 1996 ;Maki et al, 1996), but the significance of these changes (or the large number of nonconservative changes in the E1 and E2 ORFs) must be determined by functional studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, compared to the HPV-16R sequence, CaSki HPV-16 has no frameshift or nonsense mutations in any ORFs, and none of the nucleotide changes in CaSki HPV-16 alter established HPV-16 splice donor or acceptor sites, polyadenylation signals or transcription factor binding motifs (Human Papillomaviruses, 1995). The nucleotide changes in the CaSki HPV-16 SNR in full-length genomes could decrease mRNA stability or affect late promoter activity (Geisen & Kahn, 1996 ;Maki et al, 1996), but the significance of these changes (or the large number of nonconservative changes in the E1 and E2 ORFs) must be determined by functional studies.…”
Section: Discussionmentioning
confidence: 99%
“…third of the mutations and the single nucleotide deletion are concentrated in noncoding regions, with all of the changes in the short noncoding region (SNR) (Maki et al, 1996) [also referred to as the late upstream region or LUR (Geisen & Kahn, 1996)] occurring within a 51 nt span. The estimated copy number of the HPV-16 variant in CaSki cells is 60-600 (Yee et al, 1985), yet no evidence of heterogeneity at any nucleotide position in the sequenced CaSki HPV-16 amplicons was found.…”
Section: Sequencing Of the Bulk Hpv-16 Dna Amplified From Caski And Smentioning
confidence: 99%
“…Differences in the activities of constructs pHPV18(2613-3042), pHPV18(2816-3196), and pHPV18 (2816-3042) were not statistically significant. Construct pHPV18 (3930-4188) containing the fragment from nucleotide position 3930 to 4188, which has been shown by Geisen and Kahn [1996] to display promoter activity, was included as a positive control. Using this fragment, Geisen and Kahn had shown that there is a late promoter located in the E5 ORF.…”
Section: In Vivo Activity Of the Promoter In The E2 Region Of Hpv-18mentioning
confidence: 99%
“…Braunstein et al [1999] identified and characterized two additional promoters, P 482 and P 542 , located at the 3 0 -end of the HPV-16 E6 ORF. Two different laboratories have demonstrated independently that in both HPV-16 and HPV-18, a promoter exists in the region immediately upstream of the L2 ORF; this promoter is located between 4118 and 4196 in HPV-16 and between 4158 and 4188 in HPV-18 [Geisen and Kahn, 1996;Maki et al, 1996]. Karlen and Beard [1993] have identified three promoters in the HPV-18 genome: P 5600 located at the end of the L2 ORF, P 2598 located within the E1 ORF, and P 3036 located within the E2 ORF.…”
Section: Introductionmentioning
confidence: 99%
“…Early genes are exclusively expressed in the lower stratum, whereas genes encoding for the structural proteins are expressed only in the upper highly differentiated stratus [1][2][3] . In HPV-positive pre-malignant lesions, the viral E2 protein is the main regulator of early gene expression.…”
Section: Introductionmentioning
confidence: 99%